Comparative analysis of leukemia and risk estimation in working age population between provinces of Ecuador - Antonio Ramón Gómez-García; Esteban Fernandez-Moreira; Xavier García-León; Manuel Gómez del Moral (Medwave, 2024)
Leukemia is associated with exposure to radiation, benzene derivatives, and pesticides. Previous research has documented an increase in work-related leukemia in the Latin American Andean region. To date, there are only few studies in Ecuador on the impact of oil exploitation on adjacent indigenous communities. Our study aims to show the impact of leukemia on the working-age population. For the calculation of morbidity and mortality rates, we used hospital discharge and death records from the National Institute of Statistics of Ecuador. These data were collected and adjusted to the corresponding province’s population for further analysis. Large differences were observed between provinces in adjusted rates of leukemia mortality and morbidity in the working-age population. The variations in altitude among different areas in Ecuador give the provinces a distinct geographic identity. Likewise, the provinces with the highest morbidity and mortality rankings, such as Azuay, Loja, Imbabura, and Tungurahua, have an average altitude above 2000 meters. As a result, there are variations in the average temperature, exposure to solar and cosmic radiation, and mining and farming methods. The observed differences warrant the future collection of geolocation data for affected individuals. This could help to better understand how leukemia cases have demographic hotspots in the country, identify possible risk factors associated with the disease in each region, and design more effective prevention and control strategies.